Pengembangan Virtual Expo Interaktif Berbasis UI/UX Dengan Figma Di PT. Indocement Tunggal Prakarsa - Syamil Shofiyyur Rahhman; Rickman Roedavan; Agus Pratondo (Journal of Applied Engineering and Social Science (JAESS), 2024)
This project discusses the development of an interactive Virtual Expo based on UI/UX using the Figma application atPT. Indocement Tunggal Prakarsa. The interactive Virtual Expo is a virtual platform designed to replace physical exhibition events within the company. Users can explore various exhibition areas, access product information, and interact withexhibition materials virtually. The development utilizes the Figma application, which is a collaborative and intuitive UI/UXdesign tool. The project follows the Multimedia Development Life Cycle (MDLC) method, consisting of initialization, blueprintdesign, asset preparation, product development, testing, and validation. The Black Box Testing and System Usability Scale(SUS) testing results showed that this project achieved an average score of 68, indicating that the Adjective Rating for theinteractive Virtual Expo application is ”Okay” and falls into Grade C based on the SUS score interpretation guidelines. Byemploying this method, the project aims to have feature designs that can be optimally used and attract users, ensuring easyaccessibility to the interactive Virtual Expo at PT. Indocement Tunggal Prakarsa.